Respuesta :
This equation is y = mx + b, where m is the slope.
If y = mx + b is ?// to y = - 3x + 7, that means they have the SAME SLOPE, so
y = - 3x + b. To calculate b, plug in the related value of (2,-4)
- 4 = - 3(2) + b
- 4 = - 6 + b and b = -4 + 6 = +2
Hence the final equation is y = -3x +2
If y = mx + b is ?// to y = - 3x + 7, that means they have the SAME SLOPE, so
y = - 3x + b. To calculate b, plug in the related value of (2,-4)
- 4 = - 3(2) + b
- 4 = - 6 + b and b = -4 + 6 = +2
Hence the final equation is y = -3x +2
Answer:
Y= -3x+2 ...
Step-by-step explanation:
For apex as well ....
:)